Grasslands on Bellary Black Cotton Soils - Chinnamani, S. (Indian Forester, 1968)
An ecological study of the grasslands of Bellary is reported. The investigations confirm the earlier findings and typify the group as a distinct sub-type under Sehima Dichanthium type. Composition, species, production evaluation and economic data are presented. The possibility of a large scale grassland farming under rainfed condition is indicated.